PENGARUH PENDEKATAN PEMBELAJARAN KONTEKSTUAL BERBANTUAN MEDIA VISUAL TERHADAP PENINGKATAN MOTIVASI BERPRESTASI DAN HASIL BELAJAR IPA PADA SISWA - Ni Ketut Erna Muliastrini (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2021)
This study aims to determine the magnitude of the influence of the contextual learning model assisted by visual media to increase achievement motivation and science learning outcomes in students. This research is a quasi-experimental research with the design of The Posttest-Only Control-Group Design. The study population was all fourth grade elementary school students in Cluster II Abang District, Karangasem Regency in the 2019/2020 school year. Based on the characteristics of the population and individual randomization cannot be done, the sampling in this study was the group random sampling technique. Student achievement motivation data were collected using a questionnaire and science learning outcomes using multiple choice tests. Data were analyzed using MANOVA (Multivariate Analysis of Variance) assisted by SPSS 17.00 for windows. The results showed that: First, there is a significant difference in achievement motivation between students who learn with contextual learning assisted by visual media and students who learn using conventional learning models in class IV SD students in Cluster II Abang District. Second, there are significant differences in science learning outcomes between students who learn with contextual learning assisted by visual media and students who learn with conventional learning models in grade IV SD students in Cluster II Abang District. Third, simultaneously there is a significant difference in achievement motivation and science learning outcomes between students who learn with contextual learning assisted by visual media and students who learn using conventional learning models in grade IV SD students in Cluster II Abang District.